Determinants of Customer Loyalty Between TikTok Shop Users in Bali: The Role of Customer Satisfaction Moderation - A.A. Ngurah Bisma Prasatria; Nyoman Sri Subawa (Digital Innovation : International Journal of Management, 2026)
The rapid growth of social commerce has intensified competition among e-commerce platforms, making customer loyalty essential for long-term competitiveness. This study examines the effects of e-service quality, perceived ease of use, and brand image on customer loyalty among Generation Z TikTok Shop users in Bali. It also investigates the mediating role of brand image and the moderating role of customer satisfaction. The study was conducted from January to May 2026 with 250 respondents selected through purposive sampling. Primary data were collected through an online questionnaire using Google Forms and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that e-service quality, perceived ease of use, and brand image have positive and significant effects on customer loyalty. E-service quality and perceived ease of use also significantly enhance brand image. Furthermore, brand image significantly mediates the effects of e-service quality and perceived ease of use on customer loyalty. Customer satisfaction significantly strengthens the relationships between e-service quality, perceived ease of use, brand image, and customer loyalty. These findings highlight the importance of service quality, usability, brand image, and customer satisfaction in strengthening loyalty and competitive positioning in social commerce.